2012
DOI: 10.1136/neurintsurg-2012-010439
|View full text |Cite
|
Sign up to set email alerts
|

Venous sinus manometry and intervention using the PrimeWire Prestige pressure guidewire: technique and initial experience

Abstract: The PrimeWire Prestige pressure guidewire system provided a safe, fast and effective method for intracranial venous sinus manometry and intervention. It has several potential advantages over the traditional microcatheter method, including efficiency, accuracy and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Using our technique, there were no wire-related complications. Other studies also support the safety of using a pressure wire in the cerebral venous system (10,11,15,16). We also noticed that the wire was in full agreement with the microcatheter system on patients with pressure gradients equal to or >8 mm Hg, which is currently the formal indication for venous stenting (100% sensitivity).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Using our technique, there were no wire-related complications. Other studies also support the safety of using a pressure wire in the cerebral venous system (10,11,15,16). We also noticed that the wire was in full agreement with the microcatheter system on patients with pressure gradients equal to or >8 mm Hg, which is currently the formal indication for venous stenting (100% sensitivity).…”
Section: Discussionsupporting
confidence: 74%
“…Dual-sensor pressure wires have been routinely used for over 20 years in the cardiology field for gradient measurement over stenotic lesions (13). Over the past 10 years, only a few case reports and case series have studied the safety and possible accuracy of using a pressure wire for measurements of brain vasculature (10,11,(14)(15)(16). Since doubts exist regarding the accuracy of catheter-based venous measurement, we decided, in our medical center, to perform both catheter and pressure wire measurements in all cases before making the decision to deploy a stent in the venous system.…”
Section: Introductionmentioning
confidence: 99%
“…35 The PrimeWire Prestige pressure guide wire system provided a safe and effective method for intracranial venous sinus manometry. 10 The present study demonstrated moderate differences between venous manometry obtained by the microcatheter and pressure wire, especially in terms of trans-stenosis pressure gradients and pressure of the proximal stenosis. Overall, venous pressure measurements were higher when obtained by the microcatheter, but MVPs in the torcula and pressure of the distal stenosis were similar between venous manometry measured with the microcatheter and pressure wire.…”
Section: Discussionmentioning
confidence: 47%
“…35 The PrimeWire Prestige pressure guide wire system provided a safe and effective method for intracranial venous sinus manometry. 10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation